AGE OF MIDAS: NEW WORLD ORDER - Teleshun (Телешун Ярослав Сергійович), Yaroslav (Politology bulletin, 2020)
Corruption is an unchanging and “faithful” companion of the humanity accompanying it since ancient times. And like any product of mankind, it isn’t a static phenomenon and develops in parallel with the complication of human relations. With the globalization the corruption has transformed and acquired new features that make it possible to classify it likes “global corruption”. We assume that in today’s world, global corruption is a stabilizing mechanism of the modern model of world order and a safeguard against the destruction of non-viable forms of human coexistence.There are three main reasons for the inequality of income distribution in the world: 1) the existence of so-called “tax havens” – offshore zones that allow large-cap owners to avoid paying taxes; 2) inefficiency or unwillingness of national governments and the world community in regulating this issue; 3) the systematic business and politics interpenetration and the emergence of the newest phenomenon – the so-called “global corruption”.We argue that in such case post-Soviet States (including Ukraine and Russia) become a source and a “transit hub” for global corruption. Under the condition of systemic institutional instability existence, financial-industrial groups are losing exclusively economic features and getting new features, which allow them to be classified as financial-political groups. For such kind of corporate groups is typical the combination of economic, political, social and administrative components for the realization their private interests.We propose two development scenarios of corruption interconnection between financial-industrial groups and public authorities in States with unstable institutional environment: 1) complete subordination of political and economic activities of financial-industrial groups to the will of the State – “occupation of business” (for example in the Russian Federation); 2) “seizure of power” by financial-industrial groups and their further transformation into financial-political groups (for example in Ukraine). We are convinced that in such circumstances corruption can be used by some Sates as an effective tool for the political process’ influence of other countries.

Корупція — незмінний і «вірний» супутник людства з давніх часів і по сьогоднішній день. Як і будь-яке явище, породжене людською діяльністю, корупція не є статичною та еволюціонує паралельно з ускладненням людських відносин. Під натиском глобалізації «традиційна» корупція набуває нових ознак, що дозволяють класифікувати її як «глобальну корупцію». Ми припускаємо, що в сучасному світі глобальна корупція є стабілізуючим механізмом сучасної моделі світового порядку та запобіжником руйнації нежиттєздатних форм людського співіснування.Визначено три головні причини нерівності розподілу доходів у світі: 1) існування так званих «податкових раїв» — офшорних зон, що дають змогувласникам великого капіталу уникати сплати податків; 2) неефективність або небажання національних урядів і світового співтовариства у регуляції цього питання; 3) системне взаємопроникнення бізнесу й політики та виникнення явища так званої «глобальної корупції».Стверджується, що держави з нестабільним інституційним середовищем, зокрема Україна й Російська Федерація, стали «транзитним хабом» глобальної корупції за посередництва фінансово-політичних груп. За умови існування системної інституційної нестабільності фінансово-промислові групи втрачають виключно економічні риси і набувають нових ознак, що дають підстави класифікувати їх як фінансово-політичні. Зазначено, що для таких корпоративних груп характерним є поєднання економічних, політичних і адміністративно-управлінських складових для реалізації приватних та галузевих інтересів.Запропоновано два характерних сценарії розвитку взаємозв’язку фінансово-промислових груп і органів державної влади в умовах нестабільного інституційного середовища: 1) повне підпорядкування політичної, економічної діяльності фінансово-промислових груп волі держави — «захоплення бізнесу» (наприклад, у Російській Федерації); 2) «захоплення влади» фінансово-промисловими групами та їхня подальша трансформація у фінансово-політичні групи (наприклад в Україні). Припущено, що за таких обставин деякі держави можуть використовувати корупцію як ефективний інструмент впливу політичного процесу на інші країни.
ДОБА МІДАСУ: НОВИЙ СВІТОВИЙ ПОРЯДОК
Keywords: corruption; oligarchs; financial-political groups; financial-industrial groups; unstable institutional environment; post-soviet space; Ukraine; Russian Federation; корупція; олігархи; фінансово-політичні групи; фінансово-промислові групи; нестабільне інституційне середовище; пострадянський простір; Україна; Російська Федерація